The Cholesterol Controversy - David P. van Velden (South African Family Practice)
The General Practitioner has a great responsibility to implement lifestyle changes in his patient population to combat the hostile environment that modern society created for the maintenance of health.This is especially true in the case of coronary heart disease (CHD). Research evidence now lends strong support to the view that CHD is largely preventable by eliminating or modification of risk factors. Our intention is to shed some light on the cholesterol controversy referring to two well-conducted studies by Dean Ornish and Michel de Lorgeril. They found that relatively simple lifestyle and dietary changes achieved greater reductions in risk of all-cause and CHD mortality in secondary prevention trials than any of the cholesterol lowering studies to date. The Family Physician is in the ideal position to motivate his/her patient to take control and to implement a multifactorial approach for lifestyle counselling and risk modification.